Network analysis of burnout pathways among in-field and out-of-field math-major teachers in rural China - Huo, Ming (Frontiers in Public Health, 2025)
IntroductionTeacher burnout threatens educators’ well-being and instructional quality, especially in rural schools. However, little is known about how burnout differs between in-field and out-of-field teachers with the same academic background.MethodsThis study used network analysis to examine the relationships among job demands, job resources, personal resources, and burnout symptoms in 1,879 rural teachers in China with mathematics majors, including 1,682 teaching math (in-field) and 197 teaching other subjects (out-of-field).ResultsEmotional exhaustion was the most central burnout symptom in both groups, with slightly higher centrality and stronger associations with job demands among out-of-field teachers. Job satisfaction consistently acted as a protective factor, particularly in reducing depersonalization. Although the overall network structures were similar, differences in node centrality and bridging patterns were observed.DiscussionThese findings highlight that even among teachers with identical training, out-of-field teaching creates extra burnout risks by increasing the effects of job demands. These findings underscore the importance of reducing non-instructional burdens and supporting professional identity and efficacy to mitigate teacher burnout in order to improve the educational quality in rural schools.